Alternate side [large type] : a novel - Quindlen, Anna (Random House Large Print, 2018)
Some days Nora Nolan thinks that she and her husband, Charlie, lead a charmed life--except when there's a crisis at work, a leak in the roof at home, or a problem with their twins at college. And why not? New York City was once Nora's dream destination, and her clannish dead-end block has become a safe harbor, a tranquil village amid the urban craziness. Then one morning she returns from her run to discover that a terrible incident has shaken the neighborhood, and the fault lines begin to open: on the block, at her job, especially in her marriage. With humor, understanding, an acute eye, and a warm heart, Anna Quindlen explores what it means to be a mother, a wife, and a woman at a moment of reckoning.